Time-Varying Estimates on the Openness of the Capital Account in Korea and Taiwan - Reisen, Helmut (OECD Development Centre Working Papers, 1991)
How open are the capital accounts in Korea and Taiwan? Has there been a trend towards more financial openness during the 1980s? This paper aims at answering both questions by estimating a model of interest determination first outlined by Edwards and Khan, in an extension suggested by Haque and Montiel. Use is made of a time-varying parameter estimation based on the Kalman filter technique, instead of the usual constant parameter estimation. The findings indicate a low degree of capital mobility for both Korea and Taiwan, and no trend towards more financial openness (except recently in Taiwan's interbank market). The dismantling of capital controls and of internal financial restrictions is thus likely to impose an important loss of monetary autonomy in both countries ...